P-180 Bisphenols are present in culture media used for ART and cell culture. (6th August 2021) - Vignault, C; Togola, A; Desmarchais, A; Téteau, O; Maillard, V; Bristeau, S; Binet, A; Guérif, F; Elis, S
Abstract: Study question: Do plastic laboratory consumables and cell culture media used in human ART contain bisphenols? Summary answer: Human embryo development media contained bisphenols close to the nanomolar concentration range while no release of bisphenols by plastic consumables was detected under routine conditions. What is known already: The deleterious effect of the endocrine disruptor bisphenol A (BPA) on female fertility raised concerns regarding ART outcome. BPA was detected neither in media nor in the majority of plastic consumables used in ART, however it might have already been replaced by its structural analogs, including bisphenol S (BPS). Study design, size, duration: Seventeen plastic consumables and 18 cell culture and ART media were assessed for the presence of bisphenols. Participants/materials, setting, methods: Ten different bisphenols (bisphenol A, S, AF, AP, B, C, E, F, P, and Z) were measured using an isotopic dilution according to an on-line solid phase extraction / liquid chromatography/mass spectrometry method. Main results and the role of chance: While all the plastic consumables of this study did contain bisphenols, none of them did release bisphenols under routine conditions. Moreover, 16 of the 18 cell culture and ART media assessed contained bisphenols, including 8 among the 10 media used in human ART. Five human ART media exhibited bisphenol concentrations higher than 0.8 nM and reached up to 3.2 nM (799 ng/L). Limitations, reasons for caution: Further studies are required to investigate a greater number of ART media to identify less potentially harmful ones, in terms of bisphenol content. Wider implications of the findings: As BPS has already been reported to impair oocyte quality at nanomolar concentrations, its presence in ART media, at a similar concentration range, could contribute to a decrease in the ART success rate. Thus far, there has been no regulation of these compounds in the ART context. Trial registration number: Not applicable